WARRANTY COST ANALYSIS FOR PRODUCTS PROTECTED BY LEMON LAW CONSIDERING FAILURE INTERACTION - Ikhwanul Alifin, Fakhri
Some of the finished products that we often encounter are sold with a warranty. For example, a newly purchased car is usually packaged with a maintenance warranty by calculating the distance the car has traveled. In addition to a maintenance warranty, a product's warranty forms as compensation returns in the form of money equal to the selling price. The existence of a warranty in the business activity will benefit both seller and buyer. From the seller's perspective, the warranty reduces the risk of irrational product-related claims which will result in increased costs. Meanwhile, from the buyer's perspective, the warranty reduces excess expenditure due to failures in the product purchased. Therefore, the use of the warranty policy must be beneficial to the seller and buyer. However, the warranty policy set by the manufacturer often causes excessive costs as a result of the many warranty claims made by customers. Apart from the production factors that cause product defects, the warranty cost analysis factor is often neglected by manufacturers. In fact, before establishing a warranty policy, manufacturers are required to conduct a cost analysis first to determine whether the established policy is cost-effective and cost-efficient. Therefore, warranty cost analysis is essential for a better warranty policy. Research on warranty cost analysis has been performed for a long time. Various warranty policies that are usually analyzed are the Free Replacement Warranty (FRW) Pro-Rata Warranty (PRW) with one- or two-dimensional warranty models. However, often the warranty policy does not protect buyers from subsequent failures that occurred on the product so that buyers will experience an excessive cost to rectify the failures. On the other hand, the company will lose buyers, which is likely to be a domino effect because buyers may inform other potential buyers about the case of recurring damage. One of the legal policies regarding warranty that protects buyers from subsequent failures is Lemon Law. Lemon Law was first enacted in Connecticut, USA, in 1982 and currently, it has been implemented in many countries such as Singapore, Canada, European countries, and South Korea. Lemon Law protects buyers from subsequent failures because legally when the damage occurs subsequently, the buyers can make a warranty claim in the form of a refund or replacement. Apart from that, another condition for making a warranty claim that can be considered in Lemon Law iv is when the product is experiencing downtime for more than 30 days. If the conditions for the amount of damage and downtime are met, the product will be declared in lemon condition and the buyers can claim the lemon warranty. Research on Lemon Law is still limited and has not been the main focus of researchers at this time. As previously explained, several countries have implemented the Lemon Law, especially in the sale of automotive products, that's why research on Lemon Law should be the focus of researchers. In research related to the analysis of Lemon Law warranty costs, the perspective used is based on the manufacturer. The warranty schemes used in this research are refund and replacement which based on the number of the failure. The object of this research is a multi-component product that consists of critical and non-critical components. Conditioning of the warranty period is based on two cases, namely (i) the lemon warranty period is equal to the general warranty period (WL = W) and (ii) the lemon warranty period is shorter than the general warranty period (WL <W). In addition, in this study, there is a consideration of failure interaction in each of the refund and replacement schemes. This study builds a Lemon Law warranty cost model with a mathematical model which will then be processed numerically using the Matlab R2020b software to produce an optimal lemon warranty period that can minimize the expected total warranty cost and the expected warranty cost level. Based on the results obtained, the expected total cost of the warranty and the expected level of warranty costs will tend to decrease as the limits of failure increase, while the optimal lemon period will be longer. In addition, considering the failure interaction, the results show that the cost of the warranty schemes increases when there is failure interaction consideration. Then, as the reliability of the components increases, the expected total warranty costs and the expected level of warranty costs will decrease, while the optimal lemon period will be greater. This shows that the higher the number of failure limits and component reliability, the smaller the possibility of a lemon condition occurring.